Highly elastic and flexible multi-layered carbon black/elastomer composite based capacitive sensor arrays for soft robotics. (August 2019) - Devaraj, Harish; Schober, Robert; Picard, Mathieu; Teo, Mei Ying; Lo, Cheng-Yao; Gan, Wee Chen; Aw, Kean C.
Abstract: We present a highly elastic and flexible capacitive pressure/force sensing array assembled from elastic conductive thin films of carbon black composite. A robust simple fabrication technique was used, that allows seamless and easy integration of the presented elastic carbon composite capacitive tactile (ECT) sensor architecture in a wide range of robotic. The ECT sensor architecture was made completely from highly elastic and flexible elastomers with no rigid or strain limiting elements and can reversibly deform to sense loads as small as 0.05 ​N (5 ​g). The pressure sensing patch consists of 16 tactels arranged in a 4 ​× ​4 array. The capacitive sensing elements demonstrated high levels of sensitivity of nearly 150 ​pF/MPa and repeatability with instantaneous response and virtually zero hysteresis to the applied load. The sensor shows good performance as presented in this work, and has potential for use in a wide range of robotic applications.